SANKSI PIDANA TERHADAP WARGA NEGARA ASING PELAKU PENYALAHGUNAAN IZIN TINGGAL - Ramzy, Isvandiar Muhammad (HUKMY : Jurnal Hukum, 2023)
Abuse of residence permits is a legal incident that often occurs in immigration crimes. Residence permits for foreign nationals residing in Indonesian territory are often misused by these permit holders, resulting in many cases of abuse of residence permits. The method used is normative legal research or Legal Research. The results of the study are as follows: Perpetrators of abuse of residence permits are not subject to criminal sanctions under the immigration law, namely the handling of cases is shorter, namely through administrative actions in the form of deportation, and also considering the punishment. the law is "ultimum remidium" or better known as the final action for someone who violates the law, then the Class I Immigration Office TPI Jember will provide administrative sanctions as in article 78 paragraph 3 law no. 6 of 2011 concerning Immigration states that: Foreigners who have a residence permit whose validity period has expired and are still in Indonesian territory for more than 60 (sixty) days from the period of their stay permit, are subject to immigration administrative measures in the form of deportation and detention, in the case of this needs to be tightened again in terms of supervision and sanctions for foreigners who come to Indonesia, so that violations committed by foreigners can be reduced.